2007
DOI: 10.1111/j.1466-7657.2007.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of physical and mental health in hospital nurses within the People’s Republic of China

Abstract: These findings suggest areas of concern that need to be addressed, by both hospital and nursing administration, in order to establish a positive and productive work environment for Chinese nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
3
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 25 publications
4
64
3
6
Order By: Relevance
“…Neither years as a nurse nor years working on current unit were correlated with mental ill health in Chinese nurses (Lambert et al, 2007). Similarly years in the profession were not a significant factor in the mental health of US, Japanese, Thai or Korean nurses (Lambert et al, 2004) or Jamaican nurses (Lindo et al, 2006).…”
Section: Years In the Profession And Years In Rolementioning
confidence: 98%
“…Neither years as a nurse nor years working on current unit were correlated with mental ill health in Chinese nurses (Lambert et al, 2007). Similarly years in the profession were not a significant factor in the mental health of US, Japanese, Thai or Korean nurses (Lambert et al, 2004) or Jamaican nurses (Lindo et al, 2006).…”
Section: Years In the Profession And Years In Rolementioning
confidence: 98%
“…Previous studies have reported that intragroup conflict has been associated with health-related outcomes, such as depressive symptoms [16][17][18] , burnout 19) , insomnia 20) , doctor-diagnosed psychiatric morbidity 21) , somatic symptoms 10) , heavy drinking 22) , self-reported health problems 23) , and organizational outcomes such as job dissatisfaction 17,18,24) , team performance ineffectiveness 24) , work disability 7) , and occupational injuries 25) . Although it was found in two studies that intragroup conflict was not associated with depressive symptoms 26) or sickness absence 27) , these previous findings consistently suggest that intragroup conflict is a strong predictor of psychological distress, which was defined in these studies as elevated cognitive, behavioral, emotional, and psychophysiological symptoms in people suffering from a wide range of different mental disorders 28) as well as of poor health status.…”
mentioning
confidence: 99%
“…It is the absence of verbal, physical, and social contact with patients, including lack of eye contact, decreased physical proximity, decreased time spent with the patient, and negative verbal mannerisms (Siminoff, Erlen, & Sereika, 1998). Nurses' avoidance behavior has been reported in various studies (Gutierrez, 2005;Healy & McKay, 2000;Kagan, Ovadia, & Kaneti, 2009;Lambert, Lambert, Petrini, Li, & Zhang, 2007;Mackintosh, 2007;Röndahl, Innala, & Carlsson, 2003;Tyson & Pongruengphant, 1996;Wong, Leung, & So,2001) and has been associated with repeated exposure to morally distressing situations (Gutierrez, 2005).…”
Section: Avoidance Thoughts and Behaviorsmentioning
confidence: 99%
“…While avoidance behavior has been reported in nurses working in critical care (Gutierrez, 2005), in clinics assisting with elective abortions (Hanna, 2005), in delivery rooms, gynecology units, emergency departments, surgery, operating rooms, and pediatrics (Kagan, Ovadia, & Kanetai, 2009) and multi-service clinical units (medical, surgical, intensive care, oncology, mental health) (Lambert et al, 2007), this study was specifically focused on avoidance thoughts and behaviors and moral distress in critical care and non-critical care nurses. This area has not been well-studied and the data from this study contributes to what is known about the concept of avoidance as it relates to moral distress in these populations of nurses.…”
Section: Strengths Of the Studymentioning
confidence: 99%